Hubungan Antara Kronotipe Dengan Risiko Penyakit Kardiovaskuler Pada Peserta Posyandu Lansia Di Kecamatan Kartasura - Nurkamila, Febry, Dr.Yusuf Alam Romadhon, M.Kes (2017)
Chronotipe represent the choice or preference every individual in wake up phase and its sleep to express at variation of sirkardian ritme in body. Misalignment Ritme sirkardian that happened effect of bad sleep quality, so that have the impact to body health influencing the happening of cardiovasculer disease risk. This research purpose to identify the correlation between chronotipe with cardiovasculer disease risk at elderly inwrought service post participant in Kartasura District. This research was using analytic observational design with cross sectional approach. Amount of this research respondents counted by 70 sample of elderly inwrought service post participant selected by using cluster random sampling technique. This research was started from spreading and writing of approval sheet to respondents, Morningness-Eveningness Questionaire Self-Assesment Version (MEQ-SA), and questionnaire of Jakarta Cardiovasculer Score. Data analysed by using correlation Pearson test. Chronotipe type at most was morning chronotipe type and cardiovascular disease risk at most was high risk choice. Research result was got inversed correlations that do not there were correlation between chronotipe with the risk of disease cardiovascular with r = -0,071 (p = 0,561, p>0,05). This research concluding that there was no correlation.